2015
DOI: 10.3233/jpd-150688
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Effects on Early Vocal Ultrasonic Communication Dysfunction in a PINK1 Knockout Model of Parkinson’s Disease

Abstract: Background Parkinson’s disease (PD) is a complex neurodegenerative disease with vocal communication deficits that manifest early, progress, and are largely resistant to medical interventions; however, they do respond to exercise-based speech and voice therapies. Objective and Methods To study how exercise-based vocal treatment can affect the progression of communication deficits related to PD, we studied ultrasonic vocalizations (USVs) in rats with homozygous knockout (−/−) of PINK1, a gene mutation known to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 56 publications
5
25
0
Order By: Relevance
“…Changes in vocalizations in animal models of PD have been demonstrated in several model species. Common findings in rodents with parkinsonism induced by neurotoxin or transgenesis are reduced number of calls, reduced intensity of calls, and reduced call-complexity [24, 41, 42], most of which are improved with behavioral therapy (vocal exercise) [25, 43] but not with levodopa [44]. Studies in common marmosets with neurotoxin-induced parkinsonism have only reported a reduced number of vocalizations, without performing any further acoustic analyses [45, 46, 47, 48, 49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in vocalizations in animal models of PD have been demonstrated in several model species. Common findings in rodents with parkinsonism induced by neurotoxin or transgenesis are reduced number of calls, reduced intensity of calls, and reduced call-complexity [24, 41, 42], most of which are improved with behavioral therapy (vocal exercise) [25, 43] but not with levodopa [44]. Studies in common marmosets with neurotoxin-induced parkinsonism have only reported a reduced number of vocalizations, without performing any further acoustic analyses [45, 46, 47, 48, 49].…”
Section: Discussionmentioning
confidence: 99%
“…These voice and speech deficits are mostly refractory to standard of care medical treatment (levodopa) [20] or surgical treatment (deep brain stimulation) [21, 22]. Although voice and speech changes are not commonly reported by patients with PD until the later stages of the disease [23], there is recent evidence of preclinical communication changes, both in humans [3] and in animal models [24, 25]. Study of vocal changes early in neurodegenerative diseases can result in greater understanding of disease pathology, progression, and identification of behavioral biomarkers, that could improve diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…More recent data suggest that these vocal deficits are not rescued by pharmacological dopamine replacement (levodopa) [28], but can be, as in humans, modulated by a vocal-exercise therapy [29]. In general, these deficits recapitulate findings observed in humans with PD, irregular vocal qualities that impact the ability to effectively communicate.…”
Section: Introductionmentioning
confidence: 93%
“…The SOD1-G93A transgenic rodents are validated models of oral-stage dysphagia for bulbar deficits of Amyotrophic Lateral Sclerosis [28, 32]. There are multiple models of Parkinson’s disease, including (6-OHDA)-induced DA depletion [8, 37], surgical lesions [42] and PINK KO genetic models [22, 23]. Surgical or pharmacological models of stroke in rodents have been common, but are now being developed and validated for examining dysphagia [19, 44].…”
Section: Ceteris Paribus and Understanding Pathophysiologymentioning
confidence: 99%